Effects of lacosamide, pregabalin, and tapentadol on peripheral nerve excitability: a randomized, double-blind, placebo-controlled, crossover, multicenter trial : pain medicine - Nochi, Zahra; Caspani, Ombretta; Kostenko, Anna; Möller-Grell, Niko; Schilder, Andreas; Wittayer, Matthias Sebastian; Treede, Rolf-Detlef (Anesthesiology, 2025)
Chronic pain is a leading cause of disability globally, with limited treatment options and frequent adverse effects. The IMI-PainCare-BioPain project aimed to enhance analgesic drug development by standardizing biomarkers. This study, IMI2-PainCare-BioPain-RCT1, evaluated the effects of lacosamide, pregabalin, and tapentadol on peripheral nerve excitability in healthy subjects through a randomized, double-blind, placebo-controlled crossover trial. Methods: The study included 43 healthy participants aged 18 to 45 yr. Participants underwent four treatment periods during which they received single doses of lacosamide (200 mg), pregabalin (150 mg), tapentadol (100 mg), or placebo. High-frequency stimulation was applied to induce hyperalgesia. The two primary endpoints were changes in strength–duration time constant (SDTC) in large sensory and motor fibers between lacosamide and placebo periods at the first postdose timepoint compared to baseline (60 min). Other predefined endpoints included recovery cycle, threshold electrotonus (TEd), and S2 accommodation, as well as effects of pregabalin and tapentadol. Results: Lacosamide statistically significantly reduced SDTC in large sensory fibers (mean reduction, 0.04; 95% CI, 0.01 to 0.08; P = 0.012) and in motor fibers (mean reduction, 0.04; 95% CI, 0.00 to 0.07; P = 0.039) but had no effect on small sensory fibers at the first timepoint compared to placebo. There were no effects of pregabalin and tapentadol on SDTC. Of other predefined endpoints, lacosamide produced statistically significant changes in subexcitability, S2 accommodation TEd(peak), and TEd40(Accom) in large sensory fibers. No statistically significant changes were observed in refractoriness, relative refractory period, or accommodation half-time at the first timepoint compared to placebo. Conclusions: This study demonstrates that nerve excitability testing can detect pharmacodynamic effects on large myelinated fibers in healthy subjects. Lacosamide statistically significantly reduced peripheral nerve excitability, particularly in large sensory fibers.